A study of effect of low dose atorvastatin therapy on high sensitivity C-reactive protein in patients with modifiable and non-modifiable cardiovascular risk factors in central India - Verma, Archana; Chandra, Umesh Kumar; Verma, Sandhya; Jhavar, Dharmendra; Badole, Shivshankar (International Journal of Advances in Medicine, 2019)
Background: Anti-inflammatory effects of statins have generated maximum interest, as has been demonstrated in a number of studies showing rapid decrease in CRP levels in patients of acute coronary syndromes. This CRP lowering property of statins has also translated into clinical benefits as suggested by reduction in rate of recurrent angina, recurrent myocardial infarction, and mortality. Methods: This prospective, open, and controlled study was conducted on 160 indoor and outdoor patients, for total duration of two years (2005-2006), in GMC Bhopal, MP, India. Results: In all the four groups, baseline serum hs-CRP was statistically significant (p value <0.01) higher than normal hs-CRP level. Mean reduction (%) in hs-CRP after 3 months of statin therapy was 83.6% in group A and 62.4% in group C which is highly significant (p value <0.001). In group B also, 26% hs-CRP reduction was noticed which is statistically significant (p value <0.01). Baseline hs-CRP was statistically significant high (p value <0.01) in hypertensive patients. Percentages reduction in group A (87%) and group C (66%) was statistically significant (p value <0.01). Baseline hs-CRP was statistically significant higher (p value <0.01) than normal population. After 3 months of statin therapy percentage reduction in group A and group C was statistically significant (p value <0.01). Conclusions: Low dose atorvastatin can significantly reduce CRP level in patients with risk factors for cardiovascular disease. Early initiation of low dose atorvastatin can reduce this inflammatory marker in both ACS and high risk for ACS patients and can prevent major adverse cardiac events.